Building Spring Boot apps with Kotlin - Greencroft, Matt (Manning Publications, 2019)
"Building Spring Boot Applications with the Kotlin Programming Language teaches you to write clean, concise, easily maintainable Kotlin code using Spring Boot. Watch and learn as Kotlin expert Matt Greencroft explains Kotlin syntax and its automatic benefits. You'll explore Kotlin features such as immutable variables, null-safety operators, data classes, templates, and top level functions. Then, you'll discover the design approaches that make the most of the Spring and Kotlin combination, including using Spring Boot's Hibernate framework and the Thymeleaf template engine. You'll dive into functional programming and reflection, and you'll reinforce your learning with lots of helpful examples. Throughout the course, you'll incorporate your new skills by building a real world theater booking system! With this value-rich visual learning experience, you'll be more productive and--happier!--as you confidently create amazing, robust applications with Kotlin!"--Resource description page